UJI AKTIVITAS ANTIOKSIDAN ALGA COKELAT Saragassum sp. DENGAN METODE 1,1- DIFENIL-2-PIKRIHIDRASIL (DPPH) - Anugrah P.M.D. Kamoda; Maria Nindatu; Indrawanti Kusadhiani; Eka Astuty; Halidah Rahawarin; Elpira Asmin (Fakultas Kedokteran Universitas Pattimura, 2021)
Antioxidants are chemical compounds that are naturally present in the human body, which can donate hydrogen atoms to free radicals, resulting in chain reactions and converting free radicals into stable forms. Based on the source, antioxidants can be divided into 2 namely natural antioxidants and synthetic antioxidants that can overcome the formation of free radicals. One of the natural ingredients that can overcome the formation of free radicals is the brown algae Sargassum sp. The purpose of this study was to test antioxidant activity using the 1,1-Diphenyl-2-Pikrihydrasil (DPPH) method. This research is a type of experimental laboratory research. The research methodology included and prepared ingredients, extract preparation, and antioxidant activity testing using the DPPH method. Data analysis in this study was carried out by calculating the percent (%) of activity obtained from the absorbance of the data from each concentration. After obtaining the percent (%) antioxidant activity data for each absorbance sample, the IC50 value is calculated using a non-linear regression equation by substituting y = ax + b which states the relationship between log concentration and percent (%) antioxidant activity (inhibition). The results showed 50% concentration inhibition (IC50) of brown algae Sargassum sp. is 5,864. So it can be conclude that the algae Sargassum sp. has a very active antioxidant activity.